2018
DOI: 10.1074/jbc.ra118.004636
|View full text |Cite
|
Sign up to set email alerts
|

Galectin binding to cells and glycoproteins with genetically modified glycosylation reveals galectin–glycan specificities in a natural context

Abstract: 2 The abbreviations used are: CRD, carbohydrate-recognition domain; CHO, Chinese hamster ovary; LacNAc, N-acetyllactosamine; PDB, Protein Data Bank; EPO, erythropoietin; MFI, mean fluorescence intensity; GMFI, geometrical mean fluorescence intensity; FA, fluorescence anisotropy; PI, propidium iodide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 62 publications
2
63
0
Order By: Relevance
“…35 The N-and C-terminal CRDs of Gal-9 have both been shown to bind with sub-to low-micromolar affinity to glycans. 39,40 We propose a model in which Gal-9 binds bivalently to TIM-3 in several different modes, only some of which M6903 can compete with. The tandem CRDs of Gal-9 can bind to two sites in one TIM-3 molecule, as shown in Figure 6, or act as a bridge between TIM-3 molecules to form multimeric complexes.…”
Section: Discussionmentioning
confidence: 99%
“…35 The N-and C-terminal CRDs of Gal-9 have both been shown to bind with sub-to low-micromolar affinity to glycans. 39,40 We propose a model in which Gal-9 binds bivalently to TIM-3 in several different modes, only some of which M6903 can compete with. The tandem CRDs of Gal-9 can bind to two sites in one TIM-3 molecule, as shown in Figure 6, or act as a bridge between TIM-3 molecules to form multimeric complexes.…”
Section: Discussionmentioning
confidence: 99%
“…(I) There were 122 overlapping proteins between the exogenous and transfection protocols (SI Appendix, Table S1). (37,38). Thus, we next focused our investigation on profiling N-glycans, with particular attention on assessing the abundance of N-glycans bearing the high-affinity terminal galactose monosaccharides (39).…”
Section: Validation Of Interactions Between Galectin-3 and Identifiedmentioning
confidence: 99%
“…Our data on SF lubricin O-glycan truncation in OA also bears implications on binding to galectin-3. Previous studies have indicated that galectin-3 exhibits only weak affinity to Oglycoproteins and O-glycopeptides expressing single core 1 O-glycans (Galb1-3GalNAc or NeuAcα2-3Galb1-3GalNAc) (35,45).…”
Section: Functional Implications Of Lubricin Glycosylationmentioning
confidence: 99%